Prussian blue material and preparation and application thereof
Patent Information
- Application Number
- CN202311284015.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
Smart Images

Figure SMS_1 
Figure HDA0004479196260000011 
Figure HDA0004479196260000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion battery positive electrode materials, and particularly relates to a method for preparing a high-activity low-spin iron Prussian blue material and an application thereof in a sodium ion battery. Background Art
[0002] The energy crisis and environmental problems caused by the rapid development of human society are becoming increasingly serious, leading to the vigorous development of renewable energy. However, most renewable energy sources are highly weather-dependent, so it is of great practical significance to connect and store such uncertain solar energy, tidal energy, wind energy, etc. At present, electrochemical energy storage technology occupies an important position among various energy storage technologies, and lithium-ion batteries have been widely used in portable electronic devices and electric vehicles due to their advantages such as high energy density, high output voltage, low self-discharge, no memory effect, wide operating temperature range, and fast charging and discharging. However, lithium resources are mostly distributed in South American countries and are expensive, which will affect its further development, especially its application in the field of large-scale energy storage.
[0003] Sodium resources mainly come from seawater, are widely distributed around the world, and are very cheap. Sodium-ion batteries and lithium-ion batteries have similar working principles, and the development of sodium-ion batteries can rely on the mature lithium-ion battery system. However, since sodium ions have a larger ionic radius than lithium ions, materials with larger pore structures are required to be used as positive electrode materials for sodium-ion batteries. x Fe[Fe(CN) 6 ] y □ 1-y ·mH 2 O) as a MOF material has the advantages of large gaps and wide pores, which can fully accommodate sodium ions and facilitate the insertion / extraction of sodium ions. And the two redox active centers give it a high theoretical specific capacity. However, in practical applications, low-spin Fe (Fe-C) has lower activity, and usually only a small part can participate in the reaction, resulting in a loss of specific capacity. Summary of the invention
[0004] In view of the problems in the prior art that the high-voltage charge and discharge platform of Prussian blue-based sodium-ion battery positive electrode materials is short and the specific capacity and specific energy are low, the present invention is to synthesize a Prussian blue material with high-activity low-spin iron and apply it to sodium-ion batteries to increase their high-voltage charge and discharge platform, thereby improving their specific capacity and specific energy.
[0005] The invention relates to a preparation method of a Prussian blue material with high-activity low-spin iron and application of the material in a sodium ion battery.
[0006] The composition of the Prussian blue material with high activity low spin iron is NaFeFe(CN) 6 ;
[0007] The preparation steps of the Prussian blue material with high activity low spin iron include:
[0008] 1) The precursor material PB-60 (the composition of the Prussian blue material is NaFeFe(CN)) was synthesized by coprecipitation method 6 );
[0009] 2) The precursor material PB-60 obtained in step 1) is heated to N 2 A series of Prussian blue materials with high activity and low spin iron were obtained by calcination at 200-380°C in atmosphere.
[0010] The prepared Prussian blue material with high activity and low spin iron was used as the positive electrode active material, mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, and then an appropriate amount of NMP (N-methylpyrrolidone) was added and stirred. The slurry was coated on Al foil and dried at 60°C overnight. The disc was cut as the positive electrode; the metal sodium sheet was used as the negative electrode; the whatman glass fiber membrane was used as the diaphragm; 120 μL of 1M NaClO 4 Dissolved in EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 0.5-5% FEC solution (fluoroethylene carbonate, preferably 2%-3%) as the electrolyte; using CR2016 button batteries, stacking in the order of positive electrode shell, positive electrode plate, diaphragm, electrolyte, negative electrode plate, gasket, spring sheet, and negative electrode shell, and assembling into a sodium ion battery after compaction for performance testing.
[0011] Advantages and beneficial effects of the present invention: The present invention has simple operation steps. The prepared Prussian blue material has highly active low-spin iron, which can effectively improve the capacity of the high-voltage section during the charge and discharge process, thereby obtaining a higher specific capacity and specific energy.
[0012] The series of Prussian blue materials of the present invention are firstly synthesized by coprecipitation method to prepare precursor materials, and then reacted with N 2 A series of Prussian blue materials were obtained by calcining at different temperatures under atmosphere. After high-temperature calcination, the low-spin iron of the Prussian blue material was activated and more prone to redox reactions. By testing its half-cell performance, it was found that as a positive electrode material, it can produce a longer high-voltage discharge platform, so the battery can obtain higher specific capacity and specific energy during the discharge process. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1The charge and discharge curves of Examples 1-5 and Comparative Examples 1-4 at 0.2C.
[0014] Figure 2 The charge and discharge curves of Example 3 and Examples 6-10 at 0.2C.
[0015] Figure 3 The charge and discharge curves of Example 5 and Examples 11-15 at 0.2C. DETAILED DESCRIPTION
[0016] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be used to limit the present invention.
[0017] Embodiment 1-5:
[0018] 1. Investigate the effect of different calcination temperatures on battery performance, the steps include:
[0019] 4mmol Na 4 Fe(CN) 6 10H 2 O was dissolved in 200 mL of deionized water to form solution A; 6 mmol FeSO 4 7H 2 O, 15g sodium citrate was dissolved in 200mL deionized water to form solution B; after stirring for 2h, solution A was directly poured into solution B, stirred for 15min, aged at room temperature for 6h, then the supernatant was removed, and the solid residue was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at 60°C for vacuum drying overnight (12h) to obtain the PB-60 precursor material. Then the PB-60 material was placed in N 2 Under the atmosphere, the temperature was increased from room temperature to 250°C, 275°C, 300°C, 325°C, and 350°C at a rate of 2°C / min, and then naturally cooled to room temperature for 2 hours to obtain Prussian blue materials with high activity low-spin iron, which were named PB-250, PB-275, PB-300, PB-325, and PB-350, respectively.
[0020] The products obtained in Examples 1-5 (PB-250, PB-275, PB-300, PB-325, PB-350) were used as positive electrode active materials, respectively, and mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, and then added with an appropriate amount of NMP (N-methylpyrrolidone) to stir into slurry and then coated on Al foil (active material loading 1-2 mg cm -2 ), and then cut into 14 mm diameter discs as the positive electrode, and 120 μL of 1 M NaClO4 EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 2% FEC solution (fluoroethylene carbonate) was used as the electrolyte, a whatman glass fiber membrane was used as the diaphragm, and a disc-shaped metallic sodium with a diameter of 16 mm was used as the negative electrode. The positive electrode shell (also referred to as the end plate), positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, spring sheet, and negative electrode shell (also referred to as the end plate) were stacked in sequence, and assembled into a button cell after being pressed, and the charge and discharge test was carried out at 0.2C.
[0021] Figure 1 The charge and discharge curves of button cells assembled from the products of Examples 1-5 and Comparative Examples 1-4 at 0.2C in the first cycle are shown in Table 1. As can be seen from the figure, the total discharge specific capacities of Examples 1-5 after calcination are 131, 126, 116, 132, and 134 mAh g, respectively. -1 The total discharge capacity of all treated samples increased, with PB-350 increasing most significantly and PB-300 increasing less. In addition, the discharge capacity of Examples 1-5 on the high-voltage platform was 60, 60, 55, 64, and 65 mAh g, respectively. -1 , which are significantly improved compared with the control examples. The improvement of the high-voltage platform capacity indicates that after calcination, the low-spin iron of Examples 1-5 is activated, which helps to further improve the discharge specific energy.
[0022] 2. Investigate the effects of different heating rates and holding times on battery performance, the steps include:
[0023] Embodiment 6-10:
[0024] 4mmol Na 4 Fe(CN) 6 10H 2 O was dissolved in 200 mL of deionized water to form solution A; 6 mmol FeSO 4 7H 2 O, 15g sodium citrate was dissolved in 200mL deionized water to form solution B; after stirring for 2h, solution A was directly poured into solution B, stirred for 15min, aged at room temperature for 6h, then the supernatant was removed, and the solid residue was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at 60°C for vacuum drying overnight (12h) to obtain the PB-60 precursor material. Then the PB-60 material was placed in N 2 The temperature was raised from room temperature to 300°C at a rate of 2°C / min under N atmosphere, and then kept for 5 and 8 hours respectively, and then naturally cooled to room temperature. The obtained products were named PB-300-5h and PB-300-8h. 2Under the atmosphere, the temperature was raised from room temperature to 300°C at a rate of 3°C / min, 4°C / min, and 5°C / min, respectively, and then kept for 2 hours and naturally cooled to room temperature. The obtained products were named PB-300-3°C / min, PB-300-4°C / min, and PB-300-5°C / min, respectively.
[0025] The obtained products of Examples 6-10 (PB-300-5h, PB-300-8h, PB-300-3°C / min, PB-300-4°C / min, PB-300-5°C / min) were used as positive electrode active materials, respectively, mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, added with an appropriate amount of NMP (N-methylpyrrolidone) and stirred into slurry, and then coated on Al foil (active material loading 1-2 mg cm -2 ), and then cut into 14 mm diameter discs as the positive electrode, and 120 μL of 1 M NaClO 4 EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 2% FEC solution (fluoroethylene carbonate) was used as the electrolyte, a whatman glass fiber membrane was used as the diaphragm, and a disc-shaped metallic sodium with a diameter of 16 mm was used as the negative electrode. The positive electrode shell (also referred to as the end plate), positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, spring sheet, and negative electrode shell (also referred to as the end plate) were stacked in sequence, and assembled into a button cell after being pressed, and the charge and discharge test was carried out at 0.2C.
[0026] Figure 2 The charge and discharge curves of button cells assembled with the products obtained in Example 3 and Examples 6-10 at 0.2C in the first cycle are shown in Table 1. All examples were calcined at 300°C, but the holding time and heating rate were changed. It can be seen that when the holding time increases, the total discharge capacity gradually increases, among which PB-300-8h has the highest total discharge capacity, reaching 120mAh g -1 The discharge capacity contributed by the high-voltage platform is also higher, reaching 62 mAh g -1 This shows that a longer holding time makes the structural transformation of the material more complete, so the activation of high-spin iron is also more complete, which improves the specific capacity. When different heating rates are compared, it is found that the slower the heating rate, the higher the total discharge specific capacity, which shows that a slower reaction speed can make the structure undergo a more complete transformation, which is beneficial to the performance of capacity.
[0027] Embodiment 11-15:
[0028] 4mmol Na 4 Fe(CN) 6 10H2 O was dissolved in 200 mL of deionized water to form solution A; 6 mmol FeSO 4 7H 2 O, 15g sodium citrate was dissolved in 200mL deionized water to form solution B; after stirring for 2h, solution A was directly poured into solution B, stirred for 15min, aged at room temperature for 6h, then the supernatant was removed, and the solid residue was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at 60°C for vacuum drying overnight (12h) to obtain the PB-60 precursor material. Then the PB-60 material was placed in N 2 The temperature was raised from room temperature to 350°C at a rate of 2°C / min under N atmosphere, and then kept for 5 and 8 hours respectively, and then naturally cooled to room temperature. The obtained products were named PB-350-5h and PB-350-8h. 2 Under the atmosphere, the temperature was raised from room temperature to 350°C at a rate of 3°C / min, 4°C / min, and 5°C / min, respectively, and kept for 2 hours before naturally cooling to room temperature. The obtained products were named PB-350-3°C / min, PB-350-4°C / min, and PB-350-5°C / min, respectively.
[0029] The obtained product examples 11-15 (PB-350-5h, PB-350-8h, PB-350-3℃ / min, PB-350-4℃ / min, PB-350-5℃ / min) were used as the positive electrode and metallic sodium as the negative electrode to assemble button batteries, and charge and discharge tests were carried out at 0.2C.
[0030] The obtained products of Examples 11-15 were used as positive electrode active materials, respectively, and were mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, and then an appropriate amount of NMP (N-methylpyrrolidone) was added, stirred into slurry, and then coated on Al foil (active material loading 1-2 mg cm -2 ), and then cut into 14 mm diameter discs as the positive electrode, and 120 μL of 1 M NaClO 4 EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 2% FEC solution (fluoroethylene carbonate) was used as the electrolyte, a whatman glass fiber membrane was used as the diaphragm, and a disc-shaped metallic sodium with a diameter of 16 mm was used as the negative electrode. The positive electrode shell (also referred to as the end plate), positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, spring sheet, and negative electrode shell (also referred to as the end plate) were stacked in sequence, and assembled into a button cell after being pressed, and the charge and discharge test was carried out at 0.2C. Figure 3The charge and discharge curves of the button-type battery assembled with the products obtained in Example 5 and Examples 11-15 at 0.2C in the first cycle are shown in Table 1. All examples were calcined at 350°C, but the holding time and heating rate were changed. As the holding time increased, the specific capacity contributed by the high-voltage platform and the total discharge specific capacity both decreased slightly. This is because the structure of the Prussian blue material is more difficult to maintain under the higher 350°C treatment. Calcination for 2 hours can fully activate the low-spin iron in the Prussian blue, but longer treatment time will damage the structure, resulting in loss of capacity. When different heating rates were used, the sample heated at 2°C / min showed the highest discharge specific capacity, indicating that the structural transformation was the most complete at this heating rate and that very little structure was destroyed.
[0031] Figure 2 and Figure 3 The performance of the positive electrode material calcined at 300°C and 350°C under different calcination conditions is given, and the performance change trends are not the same, which means that when calcining at different temperatures, the most preferred heating rate and holding time are not exactly the same, which is mainly caused by whether the structural transformation is complete or whether the structure is destroyed. However, even if the calcination is not complete, or the calcination causes the structure to change, the positive electrode material prepared within the calcination conditions given in this claim still has a significantly longer high-voltage discharge platform, that is, the low-spin iron is activated, so even when the total discharge specific capacity is not much different, this type of material still has a higher specific energy and better battery performance.
[0032] Comparative Example 1:
[0033] The Prussian blue material is not calcined at high temperature, and its preparation method is as follows:
[0034] 4mmol Na 4 Fe(CN) 6 10H 2 O was dissolved in 200 mL of deionized water to form solution A; 6 mmol FeSO 4 7H 2 O, 15g sodium citrate was dissolved in 200mL deionized water to form solution B; after stirring for 2h, solution A was directly poured into solution B, stirred for 15min, and aged at room temperature for 6h, then the supernatant was removed, and the solid residue was washed with deionized water and ethanol in sequence, and then placed in a vacuum drying oven at 60°C for vacuum drying overnight (12h) to obtain PB-60 material.
[0035] The obtained product of comparative example 1 (PB-60) was used as the positive electrode active material, mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, added with an appropriate amount of NMP (N-methylpyrrolidone) to stir into a slurry, and then coated on Al foil (active material loading 1-2 mg cm -2 ), and then cut into 14 mm diameter discs as the positive electrode, and 120 μL of 1 M NaClO 4 EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 2% FEC solution (fluoroethylene carbonate) was used as the electrolyte, a whatman glass fiber membrane was used as the diaphragm, and a disc-shaped metallic sodium with a diameter of 16 mm was used as the negative electrode. The positive electrode shell (also referred to as the end plate), positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, spring sheet, and negative electrode shell (also referred to as the end plate) were stacked in sequence, and assembled into a button cell after being pressed, and the charge and discharge test was carried out at 0.2C.
[0036] The product obtained in Comparative Example 1 was assembled into a button-type battery, and the discharge capacity of the high-voltage platform at 0.2C was 35 mAh g -1 The total discharge capacity is 104 mAh g -1 The specific capacity is low, and the specific capacity contributed by the low-spin iron is significantly reduced compared with that of Examples 1-15, indicating that the activity of the low-spin iron is low.
[0037] Comparative Example 2:
[0038] The Prussian blue material is calcined at a relatively low temperature, and its preparation method is as follows:
[0039] 4mmol Na 4 Fe(CN) 6 10H 2 O was dissolved in 200 mL of deionized water to form solution A; 6 mmol FeSO 4 7H 2 O, 15g sodium citrate was dissolved in 200mL deionized water to form solution B; after stirring for 2h, solution A was directly poured into solution B, stirred for 15min, aged at room temperature for 6h, then the supernatant was removed, and the solid residue was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at 60°C for vacuum drying overnight (12h) to obtain the PB-60 precursor material. Then the PB-60 material was placed in N 2 Under the atmosphere, the temperature was raised from room temperature to 150°C at a rate of 2°C / min, kept for 2 hours and then naturally cooled to room temperature to obtain a Prussian blue material with high activity low-spin iron, named PB-150.
[0040] The product obtained in comparative example 2 (PB-150) was used as the positive electrode active material, mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, added with an appropriate amount of NMP (N-methylpyrrolidone) to stir into a slurry, and then coated on an Al foil (active material loading 1-2 mg cm -2 ), and then cut into 14 mm diameter discs as the positive electrode, and 120 μL of 1 M NaClO 4 EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 2% FEC solution (fluoroethylene carbonate) was used as the electrolyte, a whatman glass fiber membrane was used as the diaphragm, and a disc-shaped metallic sodium with a diameter of 16 mm was used as the negative electrode. The positive electrode shell (also referred to as the end plate), positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, spring sheet, and negative electrode shell (also referred to as the end plate) were stacked in sequence, and assembled into a button cell after being pressed, and the charge and discharge test was carried out at 0.2C.
[0041] Comparative Example 2: PB-60 was calcined at a lower temperature of 150°C. The sodium ion battery composed of PB-60 had a high-voltage platform discharge capacity of 39 mAh g at 0.2C. -1 , which is slightly different from the uncalcined comparative example 1, and significantly different from the examples 1-15, thus proving that calcination at a lower temperature is not sufficient to activate the low-spin iron.
[0042] Comparative Example 3:
[0043] Prussian blue is calcined in a non-inert atmosphere and its preparation method is as follows:
[0044] 4mmol Na 4 Fe(CN) 6 10H 2 O was dissolved in 200 mL of deionized water to form solution A; 6 mmol FeSO 4 7H 2 O, 15g sodium citrate was dissolved in 200mL deionized water to form solution B; after stirring for 2h, solution A was directly poured into solution B, stirred for 15min, aged at room temperature for 6h, then the supernatant was removed, and the solid residue was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at 60°C for vacuum drying overnight (12h) to obtain the PB-60 precursor material. Then the PB-60 material was placed in O 2 The temperature was raised from room temperature to 350°C at a rate of 2°C / min under an atmosphere, kept at this temperature for 2 hours, and then naturally cooled to obtain a Prussian blue material with high activity and low spin iron, named PB-350-O. 2 .
[0045] The obtained product (PB-350-0 2 ) was used as the positive electrode active material, mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, added with an appropriate amount of NMP (N-methylpyrrolidone) and stirred into a slurry, and then coated on Al foil (active material loading 1-2 mg cm -2 ), and then cut into 14 mm diameter discs as the positive electrode, and 120 μL of 1 M NaClO 4 EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 2% FEC solution (fluoroethylene carbonate) was used as the electrolyte, a whatman glass fiber membrane was used as the diaphragm, and a disc-shaped metallic sodium with a diameter of 16 mm was used as the negative electrode. The positive electrode shell (also referred to as the end plate), positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, spring sheet, and negative electrode shell (also referred to as the end plate) were stacked in sequence, and assembled into a button cell after being pressed, and the charge and discharge test was carried out at 0.2C.
[0046] The Prussian blue material will oxidize in an oxygen atmosphere and the product will be converted into an iron oxide material. Therefore, the specific capacity of the button battery assembled from the product obtained in Comparative Example 3 dropped sharply to only 23 mAh g -1 , proving the necessity of inert atmosphere during the synthesis process.
[0047] Comparative Example 4:
[0048] The Prussian blue material is calcined in an Ar atmosphere, and the preparation method thereof is as follows:
[0049] 4mmol Na 4 Fe(CN) 6 10H 2 O was dissolved in 200 mL of deionized water to form solution A; 6 mmol FeSO 4 7H 2 O, 15g sodium citrate was dissolved in 200mL deionized water to form solution B; after stirring for 2h, solution A was directly poured into solution B, stirred for 15min, aged at room temperature for 6h, then the supernatant was removed, the solid residue was washed with deionized water and ethanol in turn, and then placed in a vacuum drying oven at 60℃ for vacuum drying overnight (12h) to obtain the PB-60 precursor material. The PB-60 material was then placed in an Ar atmosphere, heated from room temperature to 350℃ at a rate of 2℃ / min, kept warm for 2h, and then naturally cooled to room temperature to obtain a Prussian blue material with high activity low spin iron, named PB-350-Ar.
[0050] The product obtained in comparative example 3 (PB-325-Ar) was used as the positive electrode active material, mixed with Super P (superconductive carbon black) and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, added with an appropriate amount of NMP (N-methylpyrrolidone) to stir into a slurry, and then coated on Al foil (active material loading 1-2 mg cm -2 ), and then cut into 14 mm diameter discs as the positive electrode, and 120 μL of 1 M NaClO 4 EC / DEC (ethylene carbonate / diethyl carbonate, 1:1 volume ratio) + 2% FEC solution (fluoroethylene carbonate) was used as the electrolyte, a whatman glass fiber membrane was used as the diaphragm, and a disc-shaped metallic sodium with a diameter of 16 mm was used as the negative electrode. The positive electrode shell (also referred to as the end plate), positive electrode sheet, diaphragm, electrolyte, negative electrode sheet, gasket, spring sheet, and negative electrode shell (also referred to as the end plate) were stacked in sequence, and assembled into a button cell after being pressed, and the charge and discharge test was carried out at 0.2C.
[0051] The charge-discharge curve of the Prussian blue material calcined in Ar did not change much from that before calcination. The discharge capacity of the button cell assembled from the product obtained in Comparative Example 4 was 106 mAh g -1 The discharge capacity of the high-voltage platform is 36 mAh g -1 , there is no obvious low-spin iron activation phenomenon. Table 1 shows the preparation conditions of Examples 1-15 and Comparative Examples 1-4 and the performance data of button cells.
[0052] Table 1 Effect of different calcination conditions on battery performance
[0053]
Claims
1. A method for preparing a Prussian blue material, characterized in that: The Prussian blue raw material is placed in a N2 atmosphere, heated to a calcination temperature of 200-380°C (preferably 250-350°C, more preferably 325-350°C), and kept at the calcination temperature for 2-12h (preferably 2-8h), and then cooled to obtain a high-temperature calcined product Prussian blue material.
2. The preparation method according to claim 1, characterized in that: Place a Prussian blue raw material (composed of NaFeFe(CN)6) in a N2 atmosphere and heat it from room temperature to a calcination temperature at a heating rate of 1-10°C / min (preferably 2-5°C / min); After cooling naturally to room temperature, Prussian blue material with highly active low-spin iron was obtained.
3. The preparation method according to claim 1, characterized in that: First, a Prussian blue raw material is synthesized by a coprecipitation method: 2-6 mmol Na4Fe(CN)6·10H2O (preferably 3-5 mmol) is dissolved in 100-300 mL (preferably 170-230 mL) of water to form a solution A; 3-7 mmol FeSO4·7H2O (preferably 4-6 mmol) and 10-20 g (preferably 13-18 g) of sodium citrate are dissolved in 100-300 mL (preferably 170-230 mL) of water to form a solution B; after stirring them respectively, solution A and solution B are mixed, and after being fully stirred, they are aged at room temperature for 4-10 h (preferably 5-8 h), and after removing the supernatant, the solid residue is washed, and vacuum dried at 50-80° C. (preferably 55-65° C.) for 8-24 h (preferably 10-18 h) to obtain a precursor Prussian blue raw material.
4. A Prussian blue material prepared by the preparation method according to any one of claims 1 to 3.
5. The Prussian blue material according to claim 4, characterized in that: The obtained Prussian blue material is a Prussian blue material having highly active low-spin iron.
6. Use of the Prussian blue material according to claim 4 or 5 in a sodium ion battery.
7. The use according to claim 6, characterized in that: Application of the Prussian blue material as a positive electrode active material for sodium ion batteries; The high-spin iron in the Prussian blue material is activated and has higher reactivity.
8. The use according to claim 6 or 7, characterized in that: It has a long high-voltage discharge platform, and the specific capacity contributed by the high-voltage platform exceeds 50 mAh g -1 , and the specific capacity is improved.